Estetika Fotografi Eksperimental di Masa Pandemi COVID-19: Studi Kasus Pameran Finding Horizon - Aji Susanto Anom Purnomo; Berliana Anisya Rahma (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2022)
This research aims to reveal the impact of the pandemic situation on the aesthetic aspects of the artworks in the